Surface modification of tool steel using tungsten arc heat source - Khan, TI; Khalid, FA; Orhan, N (Maney Publishing, 2004)
Many steels and, particularly, low, alloy steels, are commonly used in agricultural, transport and metal working industries. The wear resistance of such steels can be increased by employing heat treatments or surface coatings. Heat treatments are not limited to the surface and result in a change in the microstructure of the component. Therefore, although a hear resistant surface is obtained, other mechanical properties (e.g. toughness) of the substrate are compromised. When coatings are used, these have a tendency to fail along the coating/substrate interface and are lost from the surface. In tire present study, intrinsic surface modification of a tool steel (H13) is undertaken by melting using a tungsten arc heat source and gaseous alloying of the surface achieved using nitrogen gas. The change in hear resistance is compared between untreated surfaces and surfaces modified under an argon shield. Changes in the hear behaviour of the steels are characterised using pin on plate hear testing equipment. The results short, that the best wear resistance is achieved when surfaces are melted under a pure nitrogen or nitrogen-hydrogen shield. Metallurgical analysis and microindentation measurements are used to explain the differences between untreated and modified surfaces. (C) 2004 IoM Communications Ltd Publishes! by Maney for the Institute of Materials. Minerals and Mining.
Keywords: tool steel; tungsten arc; gaseous alloying; wear resistance